The prediction of the nutritive value of Mediterranean alfalfa forage by NIRS - Andueza D.; Muñoz F.; Garrido A. (Quality in lucerne and medics for animal production, 2001)
NIRS calibration equations were developed for the prediction of ash content, crude protein (CP) and neutral detergent fibre (NDF) of hays (population 1) and green forage (population 2). The results obtained show that NIRS equations explain 77-95, 93-99 and 92-90 per cent of the variation in ash, CP and NDF existing in alfalfa hays and alfalfa green forage grown in Mediterranean locations. Calibration equations for in vitro (IVDMD) and in vivo (DMD, DMO) digestibility were also obtained for green forage (population 2) and hay and dehydrated alfalfa (population 3) respectively. The equations obtained for the prediction of in vivo DMD and OMD explain 71 and 87 per cent of the variation existing in the reference data, which open great prospects for the use of NIRS in planning feeding strategies of Mediterranean livestock, based on alfalfa forage.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)